Evaluation of maxillary sinus expansion in children due to maxillary first molar extraction - Sinem Kuru; Mustafa Mert Açıkgöz; Arzu Pınar Erdem; Gülsüm Ak; Tamer Lütfi Erdem; Gamze Aren; Elif Sepet (European Oral Research, 2019)
Purpose This study is aimed at understanding the effects of maxillary first molar extraction on the expansion of maxillary sinus in children. Subjects and methods 119 patients (aged 11-17 years) who had only one extracted maxillary first molar were included in the study. The superoinferior differences of the sinus floor position were measured in both dentate and edentulous sites on panoramic radiographs. The expansion of the maxillary sinus after maxillary first molar extraction was investigated in relation to fixed anatomic structures. The interorbital line (IL) and two zygomatic process lines (IZ) were used as a reference. The vertical distances between the IL and the inferior border of the maxillary sinus (IS) in edentulous (ISX) and in dentate sites (IST) were measured. The data was analyzed statistically. Results The amount of maxillary sinus expansion in ISX was statistically significant in comparison to IST (p<0.001). The most prominent sinus expansions were found in subjects with extractions over six months prior to analysis (p<0.001). A negative correlation was detected between the amount of maxillary sinus expansion and IST (r = -0.438, p<0.001). There was a positive correlation between the amount of maxillary sinus expansion and IZT (r = 23.8, p< 0.009). Conclusion This study showed that the extraction of one maxillary first molar resulted in a negligible amount of sinus expansion in children. The results could be attributed to there being only one tooth extraction and a transferring of functional forces to the area of the neighboring teeth.